Atmospheric chemistry of oxazole: the mechanism and kinetic studies of the oxidation reaction initiated by OH radicals. (21st January 2021) - Shiroudi, Abolfazl; Abdel-Rahman, Mohamed A.; El-Nahas, Ahmed M.; Altarawneh, Mohammednoor
Abstract : Oxidation of oxazole by OH˙ radicals studied by DFT methods coupled with reaction kinetics calculations using TST and RRKM theories. Abstract : The oxidation reaction of oxazole initiated by OH radicals is studied via OH-addition and H-abstraction reactions using DFT (M06-2X and ωB97XD methods) under atmospheric conditions coupled with reaction kinetics calculations using transition state (TST) and Rice–Ramsperger–Kassel–Marcus (RRKM) theories. The obtained results show that OH˙ radical attack onto different carbons (OH-addition) proceeds faster than OH˙ attack onto H atoms bonded to the different carbons (H-abstraction) by several orders of magnitude. Furthermore, the pressure and temperature effects on the kinetic rates have been considered using RRKM calculations. Effective kinetic rate coefficients ( k eff ) demonstrate that the two-step reaction mechanism prevails. Based on the experiment, it can be concluded that the most favorable process related to hydroxyl attack onto the carbon which is adjacent to the oxygen has a lower barrier height from a kinetic viewpoint. Branching ratios (BRs) also demonstrate that the regioselectivity decreases with decreasing pressure and increasing temperature. Despite the negative energy barriers, P > 100 bar is required in order to reach the high-pressure (H-P) limit.